2020
DOI: 10.5194/egusphere-egu2020-8939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On-site Earthquake Early Warning: Predictive Models for Acceleration Response Spectra Considering Site-Effects

Abstract: <p>Including site specific amplification factors in ground motion prediction models represented an advance for PSHA (Atkinson 2006; Rodríguez-Marek et al. 2013; Kotha et al. 2017) that has become nowadays a standard. However, this issue has only recently received attention by the seismological community of earthquake early warning (EEW) (Spallarossa et al., 2019; Zhao and Zhao, 2019), which applications require a real-time prediction of ground motion and the delivery of alert message… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Nevertheless, the full investigation and explanation of the causes of these site conditions is beyond the aim of this paper. In our opinion, the significant variation in residuals shown in Figure 5A is not surprising, being in agreement with other studies (Spallarossa et al, 2019;Iaccarino et al, 2020); which have recently discussed how to reduce the prediction variability considering site-effect terms in EEW model using the mixed-effect regression approach (Pinheiro and Bates, 2000).…”
Section: Residual Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, the full investigation and explanation of the causes of these site conditions is beyond the aim of this paper. In our opinion, the significant variation in residuals shown in Figure 5A is not surprising, being in agreement with other studies (Spallarossa et al, 2019;Iaccarino et al, 2020); which have recently discussed how to reduce the prediction variability considering site-effect terms in EEW model using the mixed-effect regression approach (Pinheiro and Bates, 2000).…”
Section: Residual Analysissupporting
confidence: 92%
“…In other words, models calibrated combining datasets from different regions are exported to further areas assuming that regional effects do not play role in the model uncertainty (Stafford, 2014). However, results of recent EEW studies (e.g., among others Spallarossa et al, 2019;Iaccarino et al, 2020) have shown the opposite; that is to say, regional characteristics can play an important role in the robustness and accuracy of the EEW predictions, leading to increase the epistemic uncertainty (Al Atik et al, 2010). For this reason, we proceeded setting four different case studies using datasets of increasing order of heterogeneity.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The decomposition of the ground motion residuals into source, path and site specific terms is of interest for a wide spectrum of applications (Al Atik and Youngs, 2014;Baltay et al, 2017;, such as the develpment of partially-or non-ergodic ground motion models for probabilistic hazard assessment, e.g. (Anderson and Brune, 1999;Atkinson, 2006;Rodriguez-Marek et al, 2013;Villani and Abrahamson, 2015;Kuehn and Scherbaum, 2016;Sahakian et al, 2019;Kotha et al, 2020); on-site early warning applications (Spallarossa et al, 2019;Iaccarino et al, 2020); characterization of source process such as monitoring the preparation phase of earthquake nucleation (Piña-Valdès et al, 2 2018;Picozzi et al, 2019) and fault healing (Bindi et al, 2018). Among the different components, the distribution of event-specific deviations from the median predictions (the so-called inter-event or between-event residuals) are connected to source processes which are only partially captured, or not described at all, by the explanatory variables used to develop the ground motion model.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate estimation of the groundmotion S a (T) values in real time can help stakeholders better design engineering applications of EEW, including those relying on risk-informed decision support systems (Cremen & Galasso, 2021). Recently, Iaccarino et al (2020) and Jozinović et al (2020) proposed data-driven methods (such as mixed-effect model and convolutional neural networks, respectively) to obtain S a (T) values for few periods using initial seconds of the arriving ground motions; however, based on the results presented in their work, the frameworks' accuracy and robustness to work efficiently in real time could be further improved.…”
Section: Introductionmentioning
confidence: 99%